MEASURING CONTAGION RISK ON BANKING SYSTEM IN THE DIGITAL ERA - Musdholifah, Musdholifah; Hartono, Ulil; Wulandari, Yulita (Universitas Muhammadiyah Yogyakarta, 2019)
As an essential institution to the practice of national payment flow, banks always confront with various risk exposures inherent in them. An interbank interactions through interbank money market might yield higher systemic risks that can lead to a default. This study aims at determining the contagion effects towards Indonesian banks. This study used 18 bank samples who provided annual reports from 2007 to 2016. The measurement of the systemic risks was performed by using financial contagion risk index and was tested using Vector Autoregression method. Results show that there was a one-way causality pattern between banks as the research samples, covering BCA with Bank Mayapada, Bank Maybank, Bank Mega, and Bank Resona Perdania and also Bank CIMB Niaga with BCA, BRI, BNI, BTN, Commonwealth Bank, J-Trust Bank, Bank KEB Hana, Bank Mega, and Bank Permata. Meanwhile, two-way causality occurs between Bank BCA and Bank Mandiri and vice versa. In addition, the impact of the risk pressure of a bank is not always positive, however, it is also negative in some cases, which means that the bank can take advantage of the shocked conditions experienced by other banks